ANALISIS PERBANDINGAN ISI BUKU TEKS SEJARAH IPS TERPADU TERBITAN ERLANGGA DAN PLATINUM - Yulina, Otra; Zafri, Zafri; Husnita, Liza (Pendidikan Sejarah, 2014)
The lesson text book is one of sources and learning media which is used by teacher and students in implementing learning process recently, the various of text book which are published by many publishers, factly there are many history text book found that does not complete the requirement as example in text book is not explained the basic concept and change movement when explain the material. To be easy this research, the problem were formulated as follow: how the material completeness illustration and how compatibility of material type on every concept component and changing of an event, based on fact, concept and also principle. The aim of the research was to know the completeness illustration material and type compatibility on IPS terpadu text book Erlangga publish and Platinum on history lesson. The research method was library study by doing collecting ofthe matters at library by analyzing a problem as research topic. The data analysis was done by using content analysis technic, it was used as a data analysis technic toÂ Â Â Â analyze a document content books and also literature which become research sources. The book which was analyzed was history text book IPS terpadu Erlangga and Platinum. The research result got both of these book did not present their material based on concept component, it was seen from progress of event based on the changing movement on Erlangga and Platinum book did not present all of changing movement, but there were lack and over on bath of them. The over of Erlangga book was explain the material summary and the lack was it did not explain the arrival of west nation completely, eventhough the over of text book Platinum was explain the arrival of west nation in Indonesia completely and itâs lock was not consistent in describing material. The compatibility of material type bused on fact, concept and principle and both of books were suitable.